Turkish parents’ attitudes towards COVID-19 vaccination of their children aged 12-17 years: A cross-sectional study - US, MAHMUT CANER (My University, 2023)
Aim: The study planned to determine the attitudes of parents with children aged 12-17 years towards vaccinating their children against COVID-19 and the relationship between these attitudes and COVID-19 vaccine literacy, perception of control of COVID-19, perception of causes of COVID-19. Material and Methods: A descriptive and cross-sectional design was implemented. Between April 2022 and September 2022, 259 parents participated in the study. Data were collected using the Attitudes Towards the COVID-19 Vaccine Scale, COVID-19 Vaccine Literacy Scale, Perception of Control of COVID-19 Scale, Perception of Causes of COVID-19 and the Information Form. Results: It was found that 44.4% of the parents had vaccinated their children against COVID-19, while 55.6% had not. A positive and significant relationship was found between the mean score of the Attitudes Towards the COVID-19 Vaccine Scale and the mean score of the COVID-19 Vaccine Literacy Scale. A positive and significant relationship was found between the mean score of the Attitudes Towards the COVID-19 Vaccine Scale and the mean score of the Perception of Control of COVID-19 Scale and the macro control subdimension. A negative and significant relationship was found between the mean score of the COVID-19 Vaccine Literacy Scale and the mean score of the Perception of Causes of COVID-19 Scale and the faith subdimension. Discussion: Parental confidence, misconceptions due to lack of knowledge and social measures defined by health authorities were effective in influencing vaccine acceptance. It was noteworthy that as vaccine literacy increased, both the reduction in misconceptions and the positive effect on families’ vaccination attitudes
Keywords: COVID-19 Vaccine; Vaccine Literacy; Vaccine Attitude; Perception Of Control; Adolescent